Genesis of Vajrayāna Caryā (SIRJANĀ – A Journal Of Arts and Art Education, 2024)
Latent intent of praxis magnifies the importance of the work performed. Arrows held by Manjuśrī needs a target defined. Seemingly a physical tool has divine objective to penetrate. Existence of humans in the cosmos is the prime mark for mystical persona.Analytical and interpretative mind of the intellectually alert has put an effort to diagnose the human nature and has come to find skandha, among many other concepts, to dissect and apply to enlighten the man of the world. With a concealed aim to alleviate the plight of the human existence the whole gamut of process has been invented in the form of worship amalgamated by symbolic manifestations to visualize and realize. Pañca skandha and pañca Buddha are merely characters or personalities in the construction of the edifice. Spirituality is the final path to reach the destination. And this is where vajrayāna caryā originates.